If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7(x + 10) = 109 Reorder the terms: 6x + 7(10 + x) = 109 6x + (10 * 7 + x * 7) = 109 6x + (70 + 7x) = 109 Reorder the terms: 70 + 6x + 7x = 109 Combine like terms: 6x + 7x = 13x 70 + 13x = 109 Solving 70 + 13x = 109 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + 13x = 109 + -70 Combine like terms: 70 + -70 = 0 0 + 13x = 109 + -70 13x = 109 + -70 Combine like terms: 109 + -70 = 39 13x = 39 Divide each side by '13'. x = 3 Simplifying x = 3
| x=-0.5+0.25y | | 16t^2-48t+8=0 | | f(x)=tan(2x) | | 12x^2+46xy=8y^2 | | 9ln(4x)=18 | | x^3+2x^2-9x+30=65 | | 10K^2-11K-6= | | secx=-2 | | 5y=20x+10 | | 8500*0.025*42=x | | 49z^2=0 | | 4x^2-8xy-3x=-6y | | 4x^2-8xy-3x=6y | | x^3+2x^2-9x+30=0 | | a^2b^2+7ab+12=0 | | 5(2x+1)=7+x | | 1+2b=12-4b-2b | | 19-(x+9)=5x-2 | | 44-9-5= | | ex+3=46 | | -y^2=-9 | | 4x^2=-81 | | -7(t+4)=21 | | 44+9+5= | | -1/4x+6=2/3x+28 | | 4x-4=32x+3 | | (5-y)(3y+2)=0 | | 3+3q=8+2q | | 2x^3y+8x^2y^2-10xy^3=0 | | (5xy)(6xy)= | | 7x+9-6x=17 | | -x^2+5x=-14 |